PENERAPAN METODE DRILL SEBAGAI UPAYA PENINGKATAN KEMAMPUAN MEMBACA SISWA PADA MATA PELAJARAN AL QUR’AN HADIS MI ISLAMIYAH SOKO GLAGAH LAMONGAN - Abdul Manan; Hidayatul Lailiyah (Universitas Islam Lamongan, 2018)
Learning al-Qur'an Is A Learning Process al-Qur'an is conveyed by educators to learners with the aim to be able to read al-Qu'an with tartil in accordance with the rules of the science of tajwid. The background of this problem is the activity of Qur'anic study Drill method that influences on the achievement of al-Qur`an Hadith. The formulation of the problem taken in this research are: (1) How far the activity of teaching the students of MI Islamiyah Soko (2) How far is the achievement of Al Qur'an Lesson Hadith students MI Islamiyah Soko ? (3) Is there any influence of Drill study activity to the achievement of al-Quran Hadith Lesson to MI Islamiyah Soko ?To answer the question, this research uses quantitative approach with data collection methods, in the form of observation guidelines, questionnaires (questionnaires) and documentation. The results showed that (1) The activity of MI Islamiyah Soko. Then ro is bigger than rt. From the above research turns out the activity of studying Driil method has an influence on the achievement of Quran Hadith lesson MI Islamiyah Soko. In other words, it can be said that the activity of studying Driil method can affect student achievement, especially the achievement of Al-Quran Hadith. The higher the activity of the children, the higher the achievement of their Qur’an Hadith lesson.